Development and Shelf Stability of Natural Fibre Rich Retort Pouch Ready to Eat Products - Vasudish, C. R.; S. Nataraj ,; Premavalli, K. S. (Journal of Pharmacy and Nutrition Sciences, 2014)
The new frontier in the food research is the role of non nutritive components in human health. In the recent past, the importance of dietary fibre in the diet has been increased as a functional ingredient which has opened up a potential market for fibre rich products. The by products available during processing of plant foods are considered as promising source of functional fibres. The aim of the present study was to develop fibre rich products using the natural fibre such as ashgourd (Benincasa hispida) fibre, with high soluble fibre fraction. Ready-to-eat fibre rich Bisi bele bath and vegetable pulav were developed with the optimization of fibre using statistical design software. Fibre, fat and spice mixtures were independent variables with the other components as fixed factors. Since the product acceptance is more dependent on volatile compound form intern the flavour, as well as depends on the test, appearance, colour, texture which are the sensory attributes, total volatiles and sensory attributes were selected as responses. While in the fibre rich vegetable pulav water, fibre and spice mixtures were the independent variables. Both the products were showing good acceptability i.e. in the case of bisi bele bhath 7.1 and in the case of vegetable pulav 6.5 on a 9 point hedonic scale after 6 months of storage at room temperature. The dietary fibre profile of bisi bele bhath was 1.1% soluble fibre and 4.4% insoluble fibre while vegetable pulav had 6.2% insoluble and 1.54% soluble fibre fraction. The products were safe and had an established shelf life of 6 months.